An Analysis of Eighth-Grade Students’ Reading Comprehension Test of Narrative Folktale at Junior High School - Dhea Arinda Salsabila; Yohanes Gatot Sutapa Yuliana; Dwi Riyanti (Universitas Islam Negeri Palopo, 2026)
Reading comprehension is a crucial skill EFL learners, yet many Indonesian junior high school students continue to struggle with understanding narrative texts, particularly in identifying main ideas, interpreting vocabulary in context, and making inferences. This study aims to describe the reading comprehension ability of eighth-grade students at SMP Qur’an Labbaik Kuburaya in understanding narrative folktale texts. A descriptive quantitative design was utilized, incorporating 30 students chosen through purposive sampling. Taken a 30-item multiple-choice test to find out the data. There were six parts to the test: main idea, particular information, order of events, reference terms, terminology in context, and making inferences. The results showed that the average score for the students was 72.22, which is a good number. The range of scores, from 46.67 to 93.33, shows how different the students' reading skills were. Literal comprehension tests showed that students did well, especially when it came to identifying specific information and remembering how events happened. This suggests that familiar folktale content helped students understand explicit literary features. However, the weakest performance was found in vocabulary in context and inference questions, suggesting that students encountered difficulties in deriving word meaning and interpreting implied ideas. These findings imply that although culturally familiar folktale narratives help support comprehension, instructional practices need to provide more emphasis on vocabulary development and inferential reasoning to further enhance students’ reading proficiency. The results are expected to be useful for teachers in designing reading instruction that integrates culturally relevant materials while focusing on higher-order reading skills.